Effect of scaffolding socratic questioning technique on the development of L2 students’ critical thinking skills in reading - Umar Baki, Nurshila (2021)
Language and critical thinking are vital skills needed in the 21st century especially with the emergence of the Fourth Industrial Revolution (Industry 4.0). Both skills complement each other. As one engages in critical thinking, the language skills develop as one continues to probe for reasons and explore a topic Previous studies demonstrated the significance of promoting thinking skills, particularly critical thinking in the L1 context. Positive changes in terms of subjects’ achievement and attitudes were observed. Recent trends in L2 context have attained similar results. On the contrary, students have become passive learners and are not used to complex thinking skills due to rote-learning, teacher-talk and the exam-oriented system practiced in most Malaysian classrooms as well as in Asian ESL context. Thus, this study attempts to evaluate the potential of scaffolding Socratic questioning strategies in reading as a method to develop students’ critical thinking skills. This quasi-experimental pretest-posttest study involves fifty-eight Form 4 students from a secondary school located in Johor, Malaysia. Students were assigned to control and treatment groups and tested at the beginning and end of a nine-lesson intervention comprising scaffolding Socratic questioning in reading activities. ANCOVA was used to measure withingroup variations for the EG and CG scores as well as an independent t-test via the Levene’s t-tests for the Equality of Variance was also conducted to test the differences of scores between the two groups. Data attained from the Cornell Critical Thinking Test Level X indicated development on participants’ critical thinking skills. The results indicated that employing critical thinking skills in reading activities has a statistically significant effect on students’ critical thinking skills. The findings have useful implications not only for researchers but also for practitioners and the English learners that critical thinking plays a vital role in reading comprehension instructions.